Industrial Policy as an Elite Conflict. Big Tech Versus ‚Industrie 4.0‘? - Hubrich, Lion (Momentum Quarterly, 2023)
This contribution demonstrates that the current renaissance of industrial policy in German political discourse is to be understood against the backdrop of unfolding elite conflicts. These conflicts emerge due to the dynamization of the political economy in digital capitalism, whose proprietary logic diffuses into wider parts of the economy. In this context, established companies form industrial-policy alliances, which are backed by the state. In this article, such collaborative efforts are not understood as purely defensive measures by otherwise helpless German industrial companies. Rather, they are scrutinized for their penetration by power interests. In projects such as 'Industry 4.0', established patterns of corporatist cooperation are called upon to create legitimacy for industrial policy support. However, this is in tension with the orientation of German companies' strategies toward globalized markets, which until a few years ago was predominantly accompanied by the demand for neo-liberal deregulation.
Keywords: digital capitalism; industrial policy; political economy